PERIOPERATIVE MANAGEMENT OF CYSTIC FIBROSIS IN PATIENTS UNDERGOING ORAL AND MAXILLOFACIAL SURGERY CARE - Spirov, Vancho; Veljanovski, Darko; Nikolovski, Bruno; Iliev, Dimitar; Baftijari, Denis; Spirova, Maja; Lazov, Kiril; Stojanova, Irena (Journal of Morphological Sciences, 2025)
Cystic Fibrosis (CF) is an autosomal recessive disorder and is considered one of the most fatal hereditary diseases. The average survival age of CF patients has significantly increased over the past 60 years, particularly with advances in neonatal and pediatric care, along with modern preventive care methods. There is a large number of CF patients who require interventions in oral and maxillofacial surgery. This paper will discuss the diagnosis, pathophysiology, and systemic complications of CF and will provide relevant information regarding the management of CF patients in oral and maxillofacial surgery. Recommendations for preoperative, perioperative, and postoperative care of these patients will be presented. Keywords : cystic fibrosis, premedication, protocol, surgery